2020
DOI: 10.5603/imh.2020.0007
|View full text |Cite
|
Sign up to set email alerts
|

Field study of anthropomorphic and muscle performance changes among elite skippers following a transoceanic race

Abstract: Background: Ocean racing has become increasingly demanding, both physically and psychologically. The aim of the study was to assess global changes after a transoceanic race. Materials and methods: Eight male sailors were evaluated pre-and post-race through anthropometric measurements (weight, skinfold, girth at different level and estimated body fat percentage), multifrequency tetrapolar bioelectrical impedance, muscular performance, visual analogic scale for perceived fatigue and Critical Flicker Fusion Frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
2
12
1
Order By: Relevance
“…As for other studies (Galvani et al 2015;Gunnarsson et al 2004;Fearnley et al 2012;Lafère et al 2020) that focus on OOS, we found many di culties in producing reliable data and scienti c evidence. The researcher himself, which was part of the crew, had to take part in the strenuous activity schedule, the space for medical devices and samples on board is limited, invasive procedures are complicated to perform because of continuous motion, electronic devices cannot be charged because electrical power is limited and needed for navigation.…”
Section: Limitations and Conclusionsupporting
confidence: 68%
See 2 more Smart Citations
“…As for other studies (Galvani et al 2015;Gunnarsson et al 2004;Fearnley et al 2012;Lafère et al 2020) that focus on OOS, we found many di culties in producing reliable data and scienti c evidence. The researcher himself, which was part of the crew, had to take part in the strenuous activity schedule, the space for medical devices and samples on board is limited, invasive procedures are complicated to perform because of continuous motion, electronic devices cannot be charged because electrical power is limited and needed for navigation.…”
Section: Limitations and Conclusionsupporting
confidence: 68%
“…They are also second messengers for many pathways, such as food intake stimuli (Paoli et al 2015). The ketogenic regimen is also related to the increase of lipid metabolism (Rubini et al 2015) which in the case of OOS is often associated with the decrease of body fat percentage and weight loss (Fearnley et al 2012;Lafère et al 2020;Ghiani et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even if data regarding physical effort during offshore sailing seem comparable with inshore activity 17 , the evidence is scarce, difficult to obtain, and limited to measuring the effects of energy expenditure and physical effort activity after the race. Weight loss, fat percentage decrease, lower limb strength, and muscle mass reduction are often reported 1 , 3 , 4 , 6 , 49 . ROS production is enhanced by exercise 21 23 , 29 , 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Energy expenditure during offshore sailing is high 3 , and it is challenging to maintain an adequate nutrient intake onboard, especially during harsh weather conditions 4 . Negative energy balance often results in weight loss, decreased body fat percentage, and reduced muscle strength, proportionally to the length of the race 5 , 6 . Proper sleep management is also essential to maintain adequate performance 7 .…”
Section: Introductionmentioning
confidence: 99%